Faktor Pemicu Pengangguran dan Inflasi terhadap Kebijakan Pemerintah di Indonesia - Dina Ambarwati; Berlian Eka Nursabrina; Nailil Mufidah Qosim; Muhammad Taufiq Abadi (JOURNAL SAINS STUDENT RESEARCH, 2024)
Unemployment is one of the problems caused by the problems caused by the economy in Indonesia by labor imbalance which shows that the number of workers is supplied exceeds the quantity of labor demanded. High unemployment rate if this occurs, it will reflect the good and bad of the economy of a country or region. Apart from that, one of the problems that is very important for a country or country to pay attention to in this area, the problem of unemployment will have an impact on various crimes, social politics and poverty. Apart from that, inflation is also a problem that is often a topic of discussion in economic circles. Inflation can be influenced by various factors, for example high public consumption patterns. Indonesia’s economy will decline if inflation is not controlled properly. To control the rate of inflation is necessary forecast of inflation rate in Indonesia. The results can be used as information for the government to prepare government policies to reduce inflation remained relatively stable. The research method used is descriptive qualitative with secondary data sources.